Sri Lanka : 2018 Article IV Consultation and the Fourth Review Under the Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Sri Lanka. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that the Sri Lankan economy is expected to normalize gradually. Following subdued growth in 2017 owing to the lingering effects of weather-related shocks, a recovery is under way as agriculture has started to rebound and growth in exports remains robust. Real GDP growth is expected to reach 4 percent in 2018 and about 5 percent over the medium term. The Central Bank of Sri Lanka has effectively curbed credit growth and stabilized inflation, despite recent pressures. However, the economy remains vulnerable to adverse domestic and external shocks, given the still sizable public debt, large refinancing needs, and low external buffers.